Fiber optic networks for distributed radio architectures: FUTON concept and operation - Monteiro, P.
The growing importance of wireless communications has been driving the research and development of advanced network architectures to enable the cost-effective support of large numbers of users at very high data rates. In this context, the FUTON project aims to fulfil the objectives of the so-called 4th Generation (4G) wireless communications through an innovative Distributed Antenna System (DAS) with centralized signal processing. An overview of the FUTON concept is presented in this paper, with emphasis on the optical link design for radio-over-fiber communication providing the virtual-MIMO functionalities between multiple remote antenna units with a centralized processing site. Also, the units being fabricated for the final demonstration are described, and some preliminary measurements are presented. © 2010 IEEE.